Isu dan cabaran pelajar kurang upaya penglihatan di institusi pengajian tinggi - Raja Nur Fakhriah Raja Zainal Badri,; Aizan Sofia Amin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Education is one of the most important aspects for every individual including people with visual impairments. Visually impaired students also have the right to a good educational opportunity to higher education. In this regard, this article explores the issues and challenges of visually impaired students in higher learning institution. This study uses a full qualitative approach, a case study in the Klang Valley. In-depth interviews were used in data collection involving 5 students with visual impairment: four males and one female. The findings showed that among the major issues faced by visually impaired students pursuing higher education in tertiary institution were self-esteem, financial and public stigma. In addition, visually impaired students also faced challenges in accessibility, peer-to-peer acceptance and difficulties in learning at the university. In conclusion, this study emphasises on issues and challenges often faced by students with visual impairments at higher learning institution so that appropriate supports and facilities can be effectively provided by the university.